Pemenuhan Kebutuhan Informasi Mahasiswa Melalui Pemrosesan Informasi di Media Sosial - Azizah Nurul Islami (Jurnal Budi Pekerti Agama Islam, 2024)
This research aims to explore how students of the Indonesian Islamic High School utilize social media to fulfill their information needs. Wilson's Information Seeking theory serves as the theoretical framework, emphasizing that information needs stem from individuals' perceived needs to acquire relevant information for specific purposes. The research method employed is descriptive quantitative with the use of a questionnaire as the data collection tool. Survey results from 93 respondents, students of the Islamic Broadcasting Communication Study Program, cohorts of 2021, 2022, and 2023, reveal that these students exhibit a high level of information processing behavior through social media to meet their information needs.